Desenvolvimento de coleção de roupas femininas para momentos íntimos. - Viana, Camilla Gracino (2013)
This monograph that I present to you is about an applied research with the main objective being the satisfaction of mature women with the development of clothes for intimate moments that can provide them more safety and better performance. From further studies on the history of underwear, body, ergonomics, anthropometry, principles and elements of design, modeling and body measurements, I aim to assure this specific public with the creation of a brand dedicated to the enhancement of body shape and sensuality of women.